Plant Biotechnology and the Environment - Maria Gallo-Meagher; Stephen G. Fulford (EDIS)
The use of plant biotechnology raises a number of environmental issues. The negative issues relative to plant biotechnology include potential harm to non-target organisms, the risk of foreign genes escaping into nature, and development of accelerated pest resistance. However, many of the effects that plant biotechnology can have on the environment are positive. This document is SS-AGR-192, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published May 2003.